Evaluation of rainfall erosivity and impact forces using strain gauges - K. Vilayvong; N. Yasufuku; R. Ishikura (Lowland Technology International, 2016)
Rainfall erosivity and impact forces are key meteorological parameters for predicting rainfall-induced hazards and disasters. Erosivity of rainfall is widely indicated by its kinetic energy or momentum that is widely derived from drop diameters or drop size distribution and velocity of raindrops. Raindrop velocity and impact forces describe the rainfall erosivity dissipated to impacting surface. These parameters are not commonly evaluated and available in practice due to cost and capability of measuring instruments. A strain gauge-based device was developed for automatic and continuous measurement of the parameters in laboratory. The strain sensor, with the aid of a portable, dynamic, and high frequency data acquisition, was calibrated to capture the falling velocity of a 4.00 mm diameter waterdrop with varying heights. Results of the falling velocities of a waterdrop against heights in this study showed a close agreement with results from literature data and equations for the falling velocity and its impact force of a waterdrop were derived. In addition, results of using the equations to derive terminal velocities and impact forces as a function of drop diameters were presented.